Pengaruh sikap, norma subyektif, dan halal image terhadap niat calon nasabah menggunakan produk perbankan syariah pada Bank Negara Indonesia Syariah (BNIS) cabang Lhokseumawe - Fuadi; Khairawati; Munandar (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2020)
This study aims to determine the effect of Attitude, Subjective Norms, and Halal image either partially or simultaneously on the intention of prospective customers to use Islamic banking products at the Bank Negara Indonesia Syariah (BNIS) Lhokseumawe branch and to find out the most dominant factors in influencing prospective customer intentions. The results showed that attitude, subjective norms, and Halal image were simultaneously significant in influencing the intention of prospective customers to use Islamic banking products. Partially each of the Attitude, Subjective Norms, and Halal image variables influence the intention of prospective customers to use Islamic banking products. Attitude variable is the most dominant variable in influencing the intention of prospective customers to use Islamic banking products.